Optimisation of induction conditions for a bacterial strain producing proinsulin aspart - I. A. Kornakov; Z. R. Khasanshina; D. A. Senichkina; A. A. Filipenko; I. S. Lunev; R. V. Drai (Биопрепараты: Профилактика, диагностика, лечение)
Diabetes poses a serious threat to the health of people around the world. Therefore, in 2021, the World Health Organisation launched the Global Diabetes Compact, an initiative aimed at improving the management and prevention of diabetes. The rapid growth in the number of diabetic patients has increased the need for insulin. Rapid-acting human insulin analogues, including insulin aspart, improve the efficacy of insulin therapy. Methods for insulin aspart production include its biosynthesis in the proinsulin form in Escherichia coli. However, the yield of the recombinant protein largely depends on the optimisation of the production process.The aim of the study was to optimise the induction conditions for an E. coli strain expressing recombinant proinsulin aspart through applying the Design of Experiment (DoE) approach to enhance bacterial cell productivity.Materials and methods. The study focused on a strain of E. coli producing proinsulin aspart. The authors planned the experiment using MODDE software and the reduced face-centred central composite design (CCF) enabling the assessment of factor interactions and the creation of design spaces. The authors carried out fermentations of the producing strain in a 5 L Biostat® B bioreactor and measured proinsulin aspart concentrations by capillary gel electrophoresis. The results were analysed using GraphPad Prism 6.Results. Using the DoE approach, the authors optimised the conditions for the growth of the producer strain and the biosynthesis of proinsulin aspart. Based on data from response surface plots for wet biomass concentration, specific productivity, and volumetric productivity, as well as plotted models, the authors established design spaces for the induction of proinsulin aspart expression in E. coli. The plotted models demonstrated high predictive power and high reproducibility of the results. The authors successfully validated the induction process for the synthesis of proinsulin aspart in a bioreactor under optimised conditions. The volumetric productivity of the strain producing proinsulin aspart increased from 3.06±0.16 g/L (conventional conditions) to 4.93±0.80 g/L (optimised conditions).Conclusions. The authors achieved a 60% increase in the volumetric yield of proinsulin aspart. The study results may be used to intensify the industrial production of insulin aspart.